The Influence of The Work Environment on Employee Work Productivity at PT. Sahih Arta Logistics - Nugraha, Rommi Marullah; Fa’uzobihi, Fa’uzobihi; Taryanto, Taryanto; Irawan, Pristanto Ria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to determine the influence of the work environment on employee productivity at PT. Sahih Arta Logistics. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used amounting to 35 employees at PT. Sahih Arta Logistics, using simple linear regression data analysis techniques. The results of this study show that there is an influence between the work environment on work productivity which has a very strong positive effect and has an influence contribution of 87.8% on work productivity variables. The results of this study are expected to contribute to future research.